Teachers’ Reflections on Incorporating Islamic Moderation in English Language Teaching - Nurkasfi Samad; Sukirman (Indonesian TESOL Journal, 2025)
The increasing role of English as a global language presents challenges for Islamic educational institutions in balancing intercultural communication with the preservation of students' religious and moral values. This study explores English teachers' reflections on incorporating Islamic moderation (al-Wasatiyyah) into English Language Teaching (ELT) within Indonesian Islamic schools. Employing a qualitative multiple-case study design, data were collected through semi-structured interviews with eight English teachers from madrasahs and pesantren-based schools selected through purposive sampling. The data were analyzed using thematic analysis. The findings reveal that teachers perceive Islamic moderation as encompassing balance, tolerance, justice, openness, and peaceful coexistence, which serve as guiding principles for classroom practice. Rather than rejecting global cultural content, teachers adopted reflective pedagogical strategies by filtering, adapting, contextualizing, and critically discussing English learning materials to ensure their compatibility with Islamic ethical values while maintaining intercultural learning objectives. Reflective practice emerged as a key mechanism enabling teachers to negotiate tensions between global English and local religious identity. However, participants also identified challenges, including limited contextualized teaching materials, dominant Western cultural representations in textbooks, and insufficient institutional support. The study concludes that integrating Islamic moderation into ELT is not merely the addition of religious content but a continuous process of ethical reflection, intercultural negotiation, and pedagogical adaptation. These findings contribute to discussions on teacher cognition, culturally responsive pedagogy, and religious moderation while offering practical implications for curriculum development, teacher education, and policy in Islamic educational contexts.